MUTU DALAM LEMBAGA PENDIDIKAN ISLAM - Zulfakar, Zulfakar (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2019)
Abstract: Management is a theory that is used as a foundation to carry out all organizational activities which have been jointly determined, in order to achieve togetherness of vision and mission in institutions, of educational institutions in particular, both in the domain of national and institutional objectives. Improving the quality of education becomes a very urgent problem, related to customers, from direct education users "learners" of society in general, to continue to improve develop all potential which is institutionally, will be facilitated by educational institutions, in the concept of decentralization of education in the management, implementation, development, and policy determinants in a structured manner, starting from the central government, provincial government, regional / city government, educational institutions to the class or teacher who directly become the main executor in the process of educational journey series. Â  Keywords: Quality, Islamic Education Institution Â 